DEVELOPING GRADED READING MATERIALS TO ENHANCE EXTENSIVE READING FOR STUDENTS OF SENIOR HIGH SCHOOL - Muhammad Fauzi Al-Baihaqi (Lingua Pedagogia, 2020)
Improving literacy and a reading habit remains a major challenge to the Indonesian education system. To achieve maximum fluency in reading, the students should not only rely on classroom activities. They need a considerable amount of exposure. Therefore, there is a need to develop self-access learning materials to enhance independent learning through extensive reading. The objectives of this research were to identify the students’ target needs, identify the learning needs, and develop self-access graded reading materials to enhance extensive reading. The study employed the procedure of materials development by Jolly and Bolitho (2011) with some adaptations. There are originally 7 main stages, however, the steps were adapted and reduced into 5 stages.  The adapted stages include needs analysis, syllabus planning, materials production, materials evaluation, and revision for the final draft. The data of this research were collected by using questionnaires and interviews. The developed materials employ three levels of difficulty based on the number of headwords and readability ease. The materials were evaluated in terms of content, language, presentation, and layout appropriateness. The results of the materials evaluation showed a good outcome according to the expert judgment results.